Gender discrimination in the Australian graduate labour market - Ian W. Li; Paul W. Miller (Institute for the Study of Labor (IZA), 2012)
This paper examines gender discrimination in the Australian graduate labour market, using data from the Graduate Destination Surveys 1999-2009. A framework of analysis provided by the overeducation/required education/undereducation literature is applied. A smaller gender wage gap is found for university graduates than that reported for all workers in earlier studies. It is shown, however, that the gender wage gap widens with the age at graduation. This pattern is argued to reflect the influence of the mismeasurement of actual labour market experience in the conventional education and experience earnings equation on the standardised gender pay gap. Female graduates are less likely to be overeducated, compared to male graduates. Overeducation, while associated with substantial penalties, is not a substantial contributor to the gender wage gap.
urn:nbn:de:101:1-201305226087
Keywords: J24; J31; J70; 330; gender; graduates; overeducation; discrimination; Lohndifferenzierung; Akademiker; Unterbeschäftigung; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Australien